Guerrilla marketing for non-profit organisations in Singapore. - Lim, Shi Min. (2010)
In the recent years, there has been an increase of use in guerrilla marketing across the industry. The use of guerrilla marketing has been especially evident in Non-Profit Organisations (NPO) worldwide due to its lower cost than traditional marketing. This low cost or no cost way to market to the public makes it even more appealing. Furthermore, the present economic situation is causing even more organisations to address the idea of guerrilla marketing. The purpose of this report is thus to introduce and recommend to NPOs, the possibilities and benefits of adopting guerrilla marketing.